Recovery heat treatment process of oriented column crystal high-temperature alloy for turbine blade of gas turbine
Through vacuum or protective atmosphere high-temperature solution treatment and multi-step aging treatment, the γ′ phase and M23C6 type carbide of the directional column crystal high-temperature alloy of the turbine blade are regulated, which solves the performance attenuation problem caused by alloy aging and significantly improves the mechanical properties and life. , and simplifies the process.
Patent Information
- Application Number
- CN202411272043.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-20
AI Technical Summary
Directional column crystal high-temperature alloys will undergo tissue aging and performance attenuation after long-term high-temperature service, resulting in a decrease in the mechanical properties and life of the turbine blades. Traditional thermal isostatic pressing technology is costly and mainly used for repairing defects, making it difficult to effectively restore the structure of the alloy. .
After high-temperature solution treatment is adopted for vacuum or protective atmosphere, combined with high-temperature, medium-temperature and low-temperature aging treatment, the crystal boundaries and intra-grain of the alloy are controlled by re-dissolving and precipitating the γ′ phase and M23C6 type carbides. The structure is formed to form two sizes of γ′ phase and small block M23C6 type carbides.
Effectively restore the mechanical properties of the alloy, improve its long-lasting life under 982℃/145MPa, and increase the microhardness to above 450HV, meeting the long-term use needs and simplifying the heat treatment process.
Smart Images

Figure CN119162524A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high-temperature alloys, and in particular relates to a recovery heat treatment process of a directional columnar crystal high-temperature alloy for gas turbine turbine blades. Background Art
[0002] The turbine blades of industrial gas turbines are subjected to the most demanding temperature, stress, environment and long-term combined effects of gas turbines, and are one of the most important key components in the thermal channel system of gas turbines. Due to the removal of transverse grain boundaries, oriented columnar crystal superalloys have good high-temperature strength, oxidation resistance, corrosion resistance and fatigue resistance, and are the core preparation materials for high-pressure turbine blades. In order to meet the high-performance requirements, this type of alloy adds a high content of refractory elements to form solid solution precipitation strengthening, and uses the precipitation strengthening of γ′ phase to further improve the high-temperature strength of the alloy. However, during the long-term high-temperature service of turbine blades, oriented columnar crystal superalloys will experience organizational aging and performance attenuation, such as coarsening and rafting of γ′ phase, precipitation of topological dense phase (TCP phase), η phase, decomposition and coarsening of grain boundary strengthening phase, and intensified element segregation, which leads to a gradual decline in its mechanical properties and life.
[0003] The cost of gas turbine blades is relatively high. Appropriate recovery heat treatment processes can optimize and restore the microstructure of high-temperature alloys, improve the mechanical properties of alloys, and extend the service life of alloy blades, which is an important way to reduce the maintenance cost of industrial gas turbines. Therefore, how to regulate the intragranular and grain boundary microstructure of oriented columnar high-temperature alloys through appropriate recovery heat treatment processes, improve the mechanical properties of alloys, and extend their service life has become a key issue. The traditional use of hot isostatic pressing technology to restore and regulate the microstructure of alloys has problems such as high cost, and is mainly used to repair defects such as holes and looseness in alloys. Summary of the invention
[0004] In order to overcome the shortcomings of the prior art, the present invention provides a recovery heat treatment process for oriented columnar crystal high-temperature alloys for gas turbine turbine blades, which can effectively improve the long-term service life of oriented high-temperature alloy materials waiting for recovery after long-term service, and the heat treatment process is simple.
[0005] The technical solution adopted by the present invention to solve the technical problem is: a recovery heat treatment process for oriented columnar crystal high-temperature alloy for gas turbine turbine blades, wherein the oriented high-temperature alloy material to be restored after service in the gas turbine turbine is subjected to vacuum or protective atmosphere high-temperature solution treatment, and then furnace cooled or air cooled to room temperature; then high-temperature aging, medium-temperature aging, and low-temperature aging are sequentially performed, and air cooling is performed to room temperature after each aging step;
[0006] The medium temperature aging treatment is to heat the alloy which has undergone high temperature aging treatment to M 23 C6 Keep the temperature at 5 to 30°C below the melting temperature of the type carbide for 1 to 4 hours, and then air cool to room temperature;
[0007] The alloy includes, by mass percentage, Cr: 13.0-15.0%, Co: 9.30-9.60%, Mo: 1.40-1.60%, W: 3.70-3.90%, Ti: 4.80-5.10%, Al: 2.90-3.10%, Ta: 2.50-3.10%, B: ≤0.02%, Zr: ≤0.004%, C: 0.05-0.1%, and the balance is Ni.
[0008] A further improvement of the present invention is that the temperature of the high temperature solution treatment is 10 to 40°C below the solid phase dissolution temperature of the alloy, the time is 1 to 2 hours, and the furnace is cooled or air-cooled to room temperature. 23 C 6 The type carbides and harmful phases are completely eliminated, the coarse γ′ phase is completely dissolved back, and small-sized irregular γ′ phase is precipitated during the cooling process.
[0009] A further improvement of the present invention is that the high temperature aging treatment is to heat the alloy that has undergone high temperature solid solution treatment to 5 to 40° C. below the γ′ complete dissolution temperature, keep the temperature for 1 to 4 hours, and then air cool to room temperature.
[0010] The low-temperature aging treatment is to heat the alloy that has undergone the medium-temperature aging treatment to 840-865° C., keep the temperature for 20-30 hours, and then air-cool to room temperature to obtain the treated alloy.
[0011] A further improvement of the present invention is that after the alloy is subjected to three-step aging treatment, there are two sizes of strengthening phase γ′ phase inside the grains. The primary γ′ phase is cubic, with an average size of 380-450nm and a volume fraction of 52-58%; the secondary γ′ phase is spherical, with an average size of 90-110nm, and a small amount of small block M is precipitated at the grain boundary. 23 C 6 Type carbide.
[0012] The beneficial effect of the present invention is that after the recovery treatment, there are two γ′ phases of different shapes and sizes in the alloy, which match and enhance the precipitation strengthening effect of the alloy; 23 C 6 The carbides and harmful phases are completely dissolved back, and a small amount of small M 23 C 6type carbides, effectively restoring the alloy's grain boundary strength and intragranular strength, and the endurance life at 982℃ / 145MPa is greatly improved compared to the service-state alloy. After long-term service, the oriented columnar crystal high-temperature alloy for gas turbine turbine blades will experience structural aging, severe coarsening of the γ′ phase within the grain, massive decomposition of MC-type carbides, and precipitation of harmful phases, resulting in a decay of mechanical properties. In order to restore the organizational order of the high-temperature alloy, it is necessary to perform a solid solution treatment on the alloy above the γ′ phase dissolution temperature. On the one hand, it promotes the dissolution of harmful phases, and on the other hand, it dissolves all the γ′ phases into the matrix, in preparation for controlling the precipitation and growth of γ′ during further aging treatment. The γ′ precipitation phase is the main strengthening phase in nickel-based high-temperature alloys, and its content and morphological characteristics affect the strength inside the grains; and the network M formed at the grain boundaries after the alloy has been in service. 23 C 6 The present invention adopts high temperature solid solution, performs effective dissolution treatment at a temperature slightly lower than the alloy solidus temperature, dissolves the precipitated phase and precipitates irregular γ′ during cooling; the solid solution treatment under this condition does not damage the macroscopic morphology of the alloy, and can effectively dissolve the harmful phase and γ′ phase. The subsequent high temperature aging is mainly to promote the growth of the irregular γ′ phase after solid solution cooling to become the final large-sized γ′; the medium temperature aging is mainly to breed M 23 C 6 The nucleation and precipitation of large-sized γ′ can further increase the size of the large-sized γ′; finally, the small-sized γ′ phase can be precipitated by low-temperature aging and the cubic degree of the large-sized γ′ phase can be adjusted to achieve a balance between the strength of the alloy columnar crystals and the grain boundaries, thereby ensuring the performance potential of the alloy.
[0013] The present invention adopts a heat treatment system combining high temperature solid solution and three-step aging to completely dissolve the coarse γ′ phase and harmful phase, effectively control the large size γ′ phase and volume content of the strengthening phase inside the grain, the size of the small size γ′ phase, M 23 C 6 Through the microstructure design and regulation of the alloy, the hardness of the service alloy is increased to more than 450HV, and the endurance life at 982℃ / 145MPa is increased to more than 240h, meeting the needs of recovery and use, and the heat treatment process is simple and easy to control. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is the morphology of the γ′ phase in the grain of the alloy of the present invention before the recovery heat treatment after service.
[0015] Figure 2 This is the morphology of the intracrystalline γ′ phase after the alloy recovery heat treatment in the present invention.
[0016] Figure 3 The grain boundary morphology of the alloy after heat treatment. DETAILED DESCRIPTION
[0017] In order to enable those skilled in the art to better understand the solutions of the present invention, the following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0018] A recovery heat treatment process for a directional columnar crystal high temperature alloy for a gas turbine blade comprises the following steps:
[0019] The alloy includes, by mass percentage, Cr: 13.0-15.0%, Co: 9.30-9.60%, Mo: 1.40-1.60%, W: 3.70-3.90%, Ti: 4.80-5.10%, Al: 2.90-3.10%, Ta: 2.50-3.10%, B: ≤0.02%, Zr: ≤0.004%, C: 0.05-0.1%, and the balance is Ni;
[0020] Step 1: high temperature solution treatment: subject the directional high temperature alloy material to be restored after long-term service in the gas turbine turbine to high temperature solution treatment in vacuum or protective atmosphere, heating to 10-40°C below the solid phase dissolution temperature of the alloy for 1-2 hours, and furnace cooling or air cooling to room temperature;
[0021] Step 2: High temperature aging treatment: heat the alloy that has undergone high temperature solution treatment to 5 to 40°C below the γ′ complete dissolution temperature for 1 to 4 hours, and then air cool to room temperature;
[0022] Step 3: Medium temperature aging treatment: Heat the alloy that has undergone high temperature aging treatment to M 23 C 6 Keep the temperature at 5 to 30°C below the melting temperature of the type carbide for 1 to 4 hours, and then air cool to room temperature;
[0023] Step 4: Low-temperature aging treatment: The alloy that has undergone medium-temperature aging treatment is heated to 840-865°C for 20-30 hours, and then air-cooled to room temperature to obtain a treated alloy.
[0024] After step 4, there are two sizes of γ′ precipitated phases inside the grains. The primary γ′ phase is cubic, with an average size of 380-450nm and a volume fraction of about 52-58%; the secondary γ′ phase is spherical, with an average size of 90-110nm; 23 C 6 The carbides and harmful phases are completely dissolved, and there are a small amount of M 23 C 6The microhardness of the alloy after recovery heat treatment is increased to about 450HV or more; the endurance life at 982℃ / 145MPa is greater than 240 hours.
[0025] The following are specific embodiments and comparative examples:
[0026] Example 1
[0027] A nickel-based high-temperature alloy within the composition range of the invention is taken, and the alloy includes, by mass percentage, Cr: 13.97%, Co: 9.36%, Mo: 1.49%, W: 3.77%, Ti: 4.93%, Al: 2.97%, Ta: 2.77%, B: 0.012%, Zr: 0.0038%, C: 0.089%, and the balance is Ni; the solidus temperature of the alloy is 1240°C, the γ′ phase is completely dissolved at a temperature of 1130°C, and the M 23 C 6 The temperature at which carbides begin to dissolve is 960°C.
[0028] The turbine blades to be restored after service were subjected to high-temperature solution treatment in a protective atmosphere using oriented columnar crystal high-temperature alloy samples. The solution treatment temperature was 1220°C, the holding time was 2 hours, and then they were air-cooled to room temperature; they were heated to 1120°C and held for 2 hours for high-temperature aging treatment, and then air-cooled to room temperature; they were then heated to 950°C and held for 2 hours for medium-temperature aging treatment, and then air-cooled to room temperature; finally, they were heated to 850°C and held for 24 hours for low-temperature aging treatment, and then air-cooled to room temperature.
[0029] Figure 1 The γ′ phase morphology in the alloy crystal of Example 1 before recovery heat treatment is shown. Before recovery heat treatment, the average size of the primary γ′ phase in the crystal is about 794 μm, the area fraction is about 56.6%, and the size of the secondary γ′ phase is about 109 μm. Figure 2 The morphology of the γ′ phase in the grain after the recovery heat treatment of Example 1 is shown. The size of the primary γ′ phase in the grain is about 393 μm, the area fraction is about 55.8%, and the size of the secondary γ′ phase is about 105 μm. It can be seen that the γ′ phase in the grain has been effectively restored after the recovery heat treatment. Figure 3 The morphology of grain boundary carbides after recovery heat treatment in Example 1 is shown. It can be seen that in addition to the broken MC-type carbides at the grain boundaries, a small amount of small M-type carbides are precipitated along the grain boundaries. 23 C 6 Type carbide.
[0030] Example 2
[0031] A nickel-based high-temperature alloy within the composition range of the invention is taken, and the alloy includes, by mass percentage, Cr: 14.08%, Co: 9.52%, Mo: 1.47%, W: 3.77%, Ti: 4.90%, Al: 2.96%, Ta: 2.76%, B: 0.012%, Zr: 0.0040%, C: 0.088%, and the balance is Ni; the solidus temperature of the alloy is 1237°C, the γ′ phase of the alloy is completely dissolved at 1125°C, and the M 23 C 6 The temperature at which type carbides begin to dissolve is 955°C.
[0032] The turbine blades to be restored after service were subjected to high-temperature solution treatment in a protective atmosphere using oriented columnar crystal high-temperature alloy samples. The solution treatment temperature was 1215°C, the holding time was 2 hours, and then they were air-cooled to room temperature; they were heated to 1120°C and kept for 2 hours for high-temperature aging treatment, and then air-cooled to room temperature; they were then heated to 945°C and kept for 3 hours for medium-temperature aging treatment, and then air-cooled to room temperature; finally, they were heated to 845°C and kept for 24 hours for low-temperature aging treatment, and then air-cooled to room temperature.
[0033] Comparative Example 1
[0034] A nickel-based high-temperature alloy within the composition range of the invention content is taken, and the alloy composition is consistent with that of Example 2. The turbine blades to be restored after service are subjected to a directional columnar crystal high-temperature alloy sample for high-temperature solution treatment in a protective atmosphere. The solution treatment temperature is 1220°C, the holding time is 2 hours, and then air-cooled to room temperature; heated to 1020°C and held for 1 hour for aging treatment, and then water-cooled to room temperature.
[0035] Comparative Example 2
[0036] A nickel-based high-temperature alloy within the composition range of the invention content is taken, and the alloy composition is consistent with that of Example 1. A sample of the oriented columnar crystal high-temperature alloy for turbine blades to be restored after service is subjected to a high-temperature solution treatment in a protective atmosphere at a temperature of 1220°C for a holding time of 2 hours, and then air-cooled to room temperature; then heated to 1120°C and held for 2 hours for aging treatment, and then air-cooled to room temperature; then heated to 850°C and held for 24 hours, and then air-cooled to room temperature.
[0037] Comparative Example 3
[0038] A nickel-based high-temperature alloy within the composition range of the invention content is taken, and the alloy composition is consistent with that of Example 1. A cast, unserved turbine blade oriented columnar crystal high-temperature alloy sample is subjected to a high-temperature solution treatment in a protective atmosphere at a temperature of 1220°C for a holding time of 2 hours, and then air-cooled to room temperature; then heated to 1120°C and kept for 2 hours for aging treatment, and then air-cooled to room temperature; then heated to 850°C and kept for 24 hours, and then air-cooled to room temperature.
[0039] Comparative Example 4
[0040] A nickel-based high-temperature alloy within the composition range of the invention content is taken, and the alloy composition is consistent with that of Example 1. A cast, unserved turbine blade directional columnar crystal high-temperature alloy sample is subjected to a high-temperature solution treatment in a protective atmosphere at a temperature of 1220°C for a holding time of 2 hours, and then air-cooled to room temperature; then heated to 1120°C for holding for 2 hours for aging treatment, and then air-cooled to room temperature; then heated to 950°C for holding for 2 hours for aging treatment, and then air-cooled to room temperature; then heated to 850°C for holding for 24 hours, and then air-cooled to room temperature.
[0041] Table 1 shows the microhardness after recovery heat treatment and the endurance life at 982°C / 145MPa of Example 1, Example 2 and Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4.
[0042] Table 1 Performance characteristics of embodiments and comparative examples
[0043]
[0044]
[0045] It can be found from Table 1 that, unlike the traditional heat treatment system, after adopting the heat treatment process of the present invention, the hardness of the oriented columnar crystal high-temperature alloy for gas turbines is greatly improved, and the endurance performance has been improved by more than double, reaching more than 80% of the performance of the heat-treated alloy, meeting the basic use requirements, while the endurance performance and microhardness of the alloy in the comparative example are improved but far less than expected.
[0046] The above specific implementation modes are used to explain the present invention rather than to limit the present invention. Any modification and change made to the present invention within the spirit of the present invention and the protection scope of the claims shall fall within the protection scope of the present invention.
Claims
1. A recovery heat treatment process for oriented columnar crystal high temperature alloy for gas turbine blades, characterized in that: The directional high-temperature alloy material to be restored after long-term service in the gas turbine turbine is subjected to vacuum or protective atmosphere high-temperature solution treatment, and then furnace-cooled or air-cooled to room temperature; then subjected to high-temperature aging, medium-temperature aging, and low-temperature aging treatment in three steps in sequence, and air-cooled to room temperature after each aging step; The medium temperature aging treatment is to heat the alloy which has undergone high temperature aging treatment to M 23 Keep the temperature at 5 to 30°C below the melting temperature of C6 carbide for 1 to 4 hours, then air cool to room temperature; The alloy includes, by mass percentage, Cr: 13.0-15.0%, Co: 9.30-9.60%, Mo: 1.40-1.60%, W: 3.70-3.90%, Ti: 4.80-5.10%, Al: 2.90-3.10%, Ta: 2.50-3.10%, B: ≤0.02%, Zr: ≤0.004%, C: 0.05-0.1%, and the balance is Ni.
2. The recovery heat treatment process of the oriented columnar crystal high temperature alloy for gas turbine blades according to claim 1, characterized in that: The microhardness of the alloy after recovery heat treatment is greater than 450 HV, and the endurance life at 982° C. / 145 MPa is greater than 240 hours.
3. The recovery heat treatment process of the oriented columnar crystal high temperature alloy for gas turbine blades according to claim 1, characterized in that: The temperature of the high temperature solution treatment is 10 to 40° C. below the solid phase dissolution temperature of the alloy, the time is 1 to 2 hours, and the treatment is furnace cooled or air cooled to room temperature.
4. The recovery heat treatment process of the oriented columnar crystal high temperature alloy for gas turbine blades according to claim 1 or 3, characterized in that: After high temperature solution treatment, M in the alloy 23 C6 carbides and harmful phases are completely eliminated, the coarse γ′ phase is completely dissolved back, and small-sized irregular γ′ phase is precipitated during the cooling process.
5. The recovery heat treatment process of the oriented columnar crystal high temperature alloy for gas turbine blades according to claim 1, characterized in that: The high temperature aging treatment is to heat the alloy that has undergone high temperature solid solution treatment to 5 to 40° C. below the γ′ complete dissolution temperature, keep the temperature for 1 to 4 hours, and then air cool to room temperature.
6. The recovery heat treatment process of the oriented columnar crystal high temperature alloy for gas turbine blades according to claim 1, characterized in that: The low-temperature aging treatment is to heat the alloy that has undergone the medium-temperature aging treatment to 840-865° C., keep the temperature for 20-30 hours, and then air-cool to room temperature to obtain the treated alloy.
7. The recovery heat treatment process of the oriented columnar crystal high temperature alloy for gas turbine blades according to claim 1, characterized in that: After three-step aging treatment, there are two sizes of strengthening phase γ′ phase inside the grains. The primary γ′ phase is cubic, with an average size of 380-450nm and a volume fraction of 52-58%; the secondary γ′ phase is spherical, with an average size of 90-110nm, and a small amount of small block M precipitates at the grain boundaries. 23 C6 type carbide.
